Integration of positive matrix factorization and water quality models for pollution source identification and water quality enhancement in rivers - Semin Kim (Applied Water Science)
Abstract Identifying the primary pollution source poses a challenge in river watersheds characterized by diverse land-cover types and mixed pollution sources. We addressed this challenge by focusing on the major tributaries influencing the water quality of the Mankyung River’s mainstream, successfully identifying the primary pollution source. Additionally, it identified the limiting nutrient for algal growth in the Mankyung River, proposing an alternative strategy to enhance water quality and mitigate algal growth. Positive matrix factorization (PMF) was employed to discern pollution sources in major tributaries, namely Jeonju-cheon and Iksan-cheon, impacting mainstream water quality. For Jeonju-cheon, pollution from urban and agricultural areas, including wastewater treatment plants, emerged as the primary source. For Iksan-cheon, pollution from urban and agricultural areas predominated. The nitrogen-to-phosphorus ratio and correlation analysis revealed that total phosphorus is the limiting factor for algal growth. Furthermore, scenarios to improve water quality and reduce algal growth were developed, and the Environmental Fluid Dynamic Code (EFDC) was used in the simulation, while the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) was used in water quality assessment. The findings demonstrated improved water quality and decreased algal blooms in the downstream Mankyung River region. This research provides a foundation for applying PMF, the EFDC, and the WQI in tracking pollution sources and enhancing water quality in rivers.